Against better judgment : irrational action and literary invention in the long eighteenth century - Manganaro, Thomas Salem, 1987- (Walker Cowen Memorial Prize., 2022)
"This book traces how, in the seventeenth and eighteenth centuries, the problem of irrational action was eliminated from philosophical discourse yet flourished in literature, resulting in new literary innovations"--